Savings, investments, debts and psychological well-being in married and cohabiting couples - Man-Yee Kan; Heather Laurie (University of Essex, Institute for Social and Economic Research (ISER), 2010)
This paper builds on the existing literature about the distribution of financial resources within the household between couple members. Using data from the British Household Panel Study (BHPS) we examine the ownership of, and amounts held in savings, investments and debts by couple members, and how these vary by individual and household characteristics. A particular focus is the extent to which financial resources derived from paid employment are allocated within the household through the ownership of assets and debts by couple members. We also examine the relationship between the ownership of assets and liabilities with individual psychological well-being.
Keywords: D3; D13; J12; J16; 330; savings; investments; debts; marriage; cohabitation; gender; intra-household allocations; psychological well-being; Ehe; Lebensgemeinschaft; Privater Haushalt; Vermögen; Sparen; Schulden; Zufriedenheit; Großbritannien